Swiss national radon database: impact of building and environmental factors - Rey, Joan F.; Berlusconi, Caterina; Pampuri, Luca; Goyette Pernot, Joëlle (Frontiers in Public Health, 2025)
Since the 1980s, radon has been recognized as a public health concern in Switzerland and internationally. In an effort to more accurately estimate the number of lung cancer cases attributable to radon exposure, Swiss health authorities initiated the creation of radon measurements into a centralized national database. As of 2025, this database comprises approximately 300,000 measurements from 150,000 buildings across the country. This study aims (1) to provide a statistical characterization of the Swiss National Radon Database, including temporal and structural aspects (e.g., number of measurements, measurement duration), and (2) to identify key environmental and anthropogenic factors influencing indoor radon concentrations, using various national datasets (e.g., geology, hydrology, climate, seismicity, soil chemistry, building characteristics). Results indicate that elevated indoor radon levels are primarily associated with the presence of uranium-rich geological formations and fault zones, particularly within karstic environments. Among building-related parameters, older constructions and lower floor levels are linked to higher radon concentrations, while building type appears to have minimal influence. Moreover, a negative correlation was observed between measurement duration and radon levels, suggesting that shorter measurements tend to overestimate long-term exposure and raising questions regarding the annual representativeness. This study provides a comprehensive overview of radon distribution patterns and their determinants, offering valuable insights for researchers and public health authorities. It contributes to the development of evidence-based strategies for radon risk assessment, management, and mitigation, both within Switzerland and in comparable international contexts.